Canopus sebagai Anggota Bintang Terbaru Zij al-Sultani Ulugh Beg dan Rujukan Penentuan Arah Kiblat - Muhammad Said Fadhel; Ahmad Izzuddin (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
Zij al-Sultani was written by Ulugh Beg in 1437 AD , that is a connection with the constellation catalog in the medieval century after the book of Fix Stars by al-S?ufi. This star catalog contains comparisons in addition to several stars that are not indexed inside the book of Fixed Star. It is far known that there are twenty-seven stars updated by Ulugh Beg in Zij al- Sult?a?ni. One of the twenty-seven stars is used to determine the direction of the Qibla for some areas of Islam. The Andalusians used Canopus, a member of the constellation Carina, to determine the direction of the Qibla. In the end, this paper is expected to be a guide to look back at the journey of hisab rukyat and Islamic astronomy. That idea not only to supporting find renewal within the development of Islamic astronomy also encourages understanding comparisons between the classical books inside the medieval century. Currently, just a little discussion may be discovered concer this catalog of Zij al-Sult?a?ni by Ulugh Beg.